A traitor in Whitehall [large type] - Kelly, Julia, 1986- (Thorndike Press large print mystery series., 2024)
"1940, England: Evelyne Redfern is working at a munitions factory when she finds herself plunged into the world of Winston Churchill's cabinet war rooms. Shortly after, one of the girls at work is murdered, and Evelyne must use all of her amateur sleuthing expertise to find the killer. But doing so puts her right in the path of David Poole, who seems determined to thwart her investigations. That is, until Evelyne finds out David's real mission is to root out a mole selling government secrets and the pair begrudgingly team up. Will Evelyne be able to find out who's been selling England's secrets and catch a killer, all while battling her growing attraction to David?"--